The modelling of the logistical network of on‐line grouped goods - Jaržemskis, Andrius (Transport, 2004)
The article investigates functional interrelations between the carriage of on‐line grouped goods and the structure of the logistical network. In order to forecast the flows of on‐line grouped goods the indirect model has been chosen which enables us to evaluate two important aspects: the first one is the evaluation of the structure of the goods origins in terms of trading regions as well as the other factors determining the formation of flows of goods. The second one is concerned with the structure of the transport network. A technological tool which helps to optimize the carriage of grouped goods is the process of planning on‐line grouped goods carriage routing in accordance with the indirect forecast of demand and supply of goods market.First Published Online: 27 Oct 2010